2022
DOI: 10.1039/d1ra06862h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sensor based on screen printed carbon electrode–zinc oxide nano particles/molecularly imprinted-polymer (SPCE–ZnONPs/MIP) for detection of sodium dodecyl sulfate (SDS)

Abstract: The foremost objective of this work is to prepare a novel electrochemical sensor-based screen-printed carbon electrode made of zinc oxide nanoparticles/molecularly imprinted polymer (SPCE–ZnONPs/MIP) and investigate its characteristics to detect sodium dodecyl sulfate (SDS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…The polymer layer on the surface of the electrodes can be applied in several ways. Most often it is done by dropping a polymer solution [ 145 ] or electropolymerization [ 137 , 146 , 147 ]. Other methods described in the literature are dispensing, inkjet printing, screen-printing, electrodeposition, electrospray, or pen-writing [ 138 ].…”
Section: Application Of Screen-printed Voltammetric Sensors For the P...mentioning
confidence: 99%
“…The polymer layer on the surface of the electrodes can be applied in several ways. Most often it is done by dropping a polymer solution [ 145 ] or electropolymerization [ 137 , 146 , 147 ]. Other methods described in the literature are dispensing, inkjet printing, screen-printing, electrodeposition, electrospray, or pen-writing [ 138 ].…”
Section: Application Of Screen-printed Voltammetric Sensors For the P...mentioning
confidence: 99%
“…Oxidation of DAP and MEROP is shown at 0.68 V and 0.97 V, respectively, indicating a signicant increase in the oxidation current at the CuNPs/SPCE compared to the value at the bare SPCE in which slight peaks of both antibiotics were observed that could be assigned to the effect of the carbon working electrode. 72 The enhancement of the oxidation peak signals at the modied electrode is due to the excellent catalytic and electrical properties of CuNPs. 73 3.2.3.…”
Section: Electrochemical Behavior Of Modied Electrodes the Ec Behavi...mentioning
confidence: 99%
“…Electrochemical techniques offer portability, inexpensive, simple preparation, and rapid measurement. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical techniques offer portability, inexpensive, simple preparation, and rapid measurement. 12,13 A mercury-based electrode is generally applied for measuring heavy metal ions using a voltammetry technique. Following environmental issues, a mercury-free electrode is preferred.…”
Section: Introductionmentioning
confidence: 99%